Muscarinic receptor subtypes of guinea-pig gallbladder smooth muscle - (:unkn) unknown (My University, 1990)
The antagonism of acetylcholine-induced contractions of guinea-pig gallbladder and ileum smooth muscle strips via various antagonists has been investigated in order to find out the muscarinic receptor subtype(s) of gallbladder smooth muscle. Atropine, pirenzepine, 4-DAMP and AF-DX 116 were used as nonselective, M1-selective, M1- and smooth muscle M3-selective and cardiac M2-selective muscarinic antagonists, respectively. All the muscarinic antagonists examined displaced the concentration-response curves to the right parallelly in a concentration-dependent manner without affecting the maximum response in both tissues. Schild analysis of data was consistent with competitive antagonism. pA2 values of the antagonists were as follows: a) gallbladder: atropine: 8.43; pirenzepine: 7.81; 4-DAMP: 8.10; AF-DX 116: 6.71; b) ileum: atropine: 9.62; pirenzepine: 6.94; 4-DAMP: 9.41; AF-DX 116: 6.55. It may be concluded that the muscarinic receptors of the guinea-pig gallbladder, which mediate acetylcholine-induced contractions, are not of the cardiac M2-subtype and may be distinguished from ileal smooth muscle M3-receptors because 4-DAMP has a 20.4 times greater affinity for ileal smooth muscle muscarinic receptors.